(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This article is devoted to improving tax administration for income tax. Income tax is an important source of government revenue and effective tax administration is essential to ensure efficient revenue collection and taxpayer compliance. This analysis looks at various aspects of tax administration that can be improved to simplify the process, reduce tax evasion and create a more business-friendly environment. The analysis includes a review of relevant literature, research and experiences from different countries. At the same time, such areas as underground trade and catering, transportation by road, housing construction and repair, provision of housing and household services in the economy were studied, and scientific and practical conclusions and proposals were formed based on foreign experience and its application in the economy. our country.